Antibacterial activity of essential oil extracts from Curcuma xanthorrhiza roxb. rhizomes against bacteria causing pulp necrosis - Dwi Prijatmoko; Nakhita L. Syafira; Pujiana E. Lestari (Journal of Dentomaxillofacial Science, 2018)
Objective: To analyze antibacterial activity of essential oil extracted from Curcuma xanthorrhiza Roxb. rhizomes against bacteria causing pulp necrosis, Enterococcus faecalis, and Fusobacterium nucleatum.Material and Methods: The method used in this research was disc-diffusion on MH-A media, based on the standard protocol of National Committee for Clinical Laboratory Standards (NCCLS). This method used 4 replications in each of the study group. The study group consists of 4 different concentration groups (25%, 50%, 75% and 100% ) of Temulawak rhizomes essential oil extracts, ChKM and Cresophene were used as the positive control group and DMSO (10%) and Tween 80 (0.5%) was used as the negative control group.Results: The inhibition zones of 25%, 50%, 75%, and 100% of temulawak rhizomes essential oil extracts against E. faecalis were 8.17 mm, 8.54 mm, 9.53 mm, and 10.17 mm, respectively. Whereas, the inhibition zones of 25%, 50%, 75%, and 100% of temulawak rhizomes essential oil extracts against F. nucleatum were 8.54 mm, 8.95 mm, 9.65 mm and 10.75 mm, respectively. Data analysis using Kruskal-Wallis in both of bacteria showed p=0.00 (p<0.05) and therefore, significant levels of inhibition.Conclusion: Essential oil extracts from C. xanthorrhiza Roxb. rhizomes has medium antibacterial activity against E. faecalis and F. nucleatum.